The Arrival Of Naqshabandi Order From Hijaz To The Malay World: 16th Until The Early 19th Century - Muhammad Khairi Mahyuddin; Zakaria Stapa; Faudzinaim Badaruddin (Center For Promoting Ideas, USA, 2024)
International Journal of Business and Social Science Vol. 4 No. 1; January 2013